Teaching English for Specific Business Purposes, Systemic- Functional Linguistics and the Register/Genre Theory - Jr., Orlando Vian (The ESPecialist, 2012)
This article aims at presenting some results on the design of an ESP speaking course taught at a major Brazilian bank located in the city of São Paulo. The course, based on systemic-functional linguistics, was designed focusing on students’ communicative needs as well as on their departmental necessities, departing from (i) the genre students were supposed to perform and (ii) the teaching of speaking from an ESP perspective. We conclude by pointing out suggestions on designing a genre-based course, as well as contributing to theoretical discussions on genre/register theory.